Cytotoxicity and Induction of Inflammation by Pepsin in Acid in Bronchial Epithelial Cells - Erik Bathoorn; Paul Daly; Birgit Gaiser; Karl Sternad; Craig Poland; William MacNee; Ellen M. Drost (International Journal of Inflammation)
Introduction. Gastroesophageal reflux has been associated with chronic inflammatory diseases and may be a cause of airway remodelling. Aspiration of gastric fluids may cause damage to airway epithelial cells, not only because acidity is toxic to bronchial epithelial cells, but also since it contains digestive enzymes, such as pepsin. Aim. To study whether pepsin enhances cytotoxicity and inflammation in airway epithelial cells, and whether this is pH-dependent. Methods. Human bronchial epithelial cells were exposed to increasing pepsin concentrations in varying acidic milieus, and cell proliferation and cytokine release were assessed. Results. Cell survival was decreased by pepsin exposure depending on its concentration (F=17.4) and pH level of the medium (F=6.5) (both P<0.01). Pepsin-induced interleukin-8 release was greater at lower pH (F=5.1; P<0.01). Interleukin-6 induction by pepsin was greater at pH 1.5 compared to pH 2.5 (mean difference 434%; P=0.03). Conclusion. Pepsin is cytotoxic to bronchial epithelial cells and induces inflammation in addition to acid alone, dependent on the level of acidity. Future studies should assess whether chronic aspiration causes airway remodelling in chronic inflammatory lung diseases.